Prospective Evaluation of a Circulating Tumor Cell Sensitivity Profile to Predict Response to Cisplatin Chemotherapy in Metastatic Breast Cancer Patients - de Kruijff, I. E.; Sieuwerts, A. M.; Beije, N.; Prager - van der Smissen, W. J. C.; Angus, L.; Beaufort, C. M.; Van, M. N.; Oomen - de Hoop, E.; Jager, A.; Hamberg, P.; de Jongh, F. E.; Kraan, J.; et al. (Frontiers in Oncology, 2021)
Background Cisplatin (cDDP) has regained interest for metastatic breast cancer (MBC) patients, given the platinum sensitivity in subtypes and better manageable toxicity. Here, the primary aim was to determine whether molecular characteristics of circulating tumor cells (CTCs) could identify patients responding to cDDP and to describe the outcomes to cDDP monotherapy in a large group of MBC patients pretreated with anthracycline- and taxane-based treatments. Methods Based on cell line data, a CTC-cDDP-sensitivity profile was generated. Applying an A’Herns single-stage phase II design, further investigation was considered worthwhile if 5/10 patients with a favorable profile responded to cDDP. Patients received 70mg/m2 cDDP every three weeks, CTCs were enumerated and CTC-cDDP-sensitivity profile was determined. In total, 65 heavily pretreated mBC patients (77% received ≥2 lines of previous chemotherapy for MBC) were eligible for the per-protocol analysis. Primary endpoint was response rate, secondary endpoints included best observed response, progression-free survival (PFS) and overall survival (OS). Results The best observed response during cDDP therapy was a partial response in 7% and stable disease in 56% of the patients. None of the patients with a favorable CTC-cDDP-sensitivity profile had a response. The median baseline CTC count was 8 (range 0-3254). Patients with <5 CTCs had a better PFS and OS than patients with ≥5 CTCs (median PFS 4.5 months (95%CI 2.38-6.62) vs. 2.1 months ((95%CI 1.34-2.80)(p=0.009)) and median OS 13.1 months (95%CI 9.89-16.33) vs. 5.6 months ((95%CI 3.60-7.64)(p=0.003)). No other factors than CTC count were associated with outcome to cDDP therapy, including triple-negative breast cancer versus ER-positive tumors. Conclusions The CTC-cDDP-sensitivity profile was unable to select patients responding to cDDP monotherapy. In an unselected group of heavily pretreated MBC patients, cDDP yields outcomes comparable to other chemotherapeutic regimens for heavily pretreated MBC patients. CTC count was the only factor associated with outcome in these patients. Trial registration Dutch Trial Register NTR4046. Registered 26 June 2013 – Retrospectively registered (first patients inclusion 7 June 2013), https://www.trialregister.nl/trial/3885.